2022
DOI: 10.1101/2022.10.21.513138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-range interactions between fibrocytes and CD8+T cells in COPD bronchial inflammatory response

Abstract: The peri-bronchial zone of chronic obstructive pulmonary disease (COPD) is the site of extensive infiltration of immune cell, allowing persistent contacts between resident cells and immune cells. Tissue fibrocytes interaction with CD8+T cells and its consequences were investigated. We show that interactions beween both cell types are more frequent in distal airways from COPD patients compared to those of control subjects. Tissular CD8+T cells from COPD patients promote fibrocyte chemotaxis via the CXCL8-CXCR1/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…These results are in agreement with findings obtained in mice treated with another CXCR4 antagonist or with CXCL12 neutralizing antibodies, in the context of pulmonary fibrosis, where reduction of fibrocytes accumulation concomitantly improved lung outcomes (13, 32). The reduction of tissue fibrocytes could thus contribute to lower chronic inflammation (33). Finally, plerixafor-induced increased mobilization of hematopoietic progenitor cells from the bone marrow may also participate in the improvement of lung function and remodeling as suggested by another study showing that plerixafor-treated mice were protected against CS-induced emphysema (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with findings obtained in mice treated with another CXCR4 antagonist or with CXCL12 neutralizing antibodies, in the context of pulmonary fibrosis, where reduction of fibrocytes accumulation concomitantly improved lung outcomes (13, 32). The reduction of tissue fibrocytes could thus contribute to lower chronic inflammation (33). Finally, plerixafor-induced increased mobilization of hematopoietic progenitor cells from the bone marrow may also participate in the improvement of lung function and remodeling as suggested by another study showing that plerixafor-treated mice were protected against CS-induced emphysema (12).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, and importantly, these fibrocytes could also perpetuate chronic inflammation, through interaction with CD8 + T cells. Such cells are indeed implicated in COPD lung pathogenesis (43) and we have recently shown that fibrocytes directly interact with CD8+ T cells in the lungs, leading to increased proliferation and activation (44).…”
Section: Discussionmentioning
confidence: 99%